Development of test tasks for assessment of listening skills in online English language school - Kail I. A. (Current trends in the development of education system, 2019)
The article attempts the features of the compilation of test tasks for assessing listening skills in an online school. The hypothesis about the correlation of the results of assessment of the listening skills by the developed test tasks and expert evaluations is tested.
Keywords: оценка; тестирование; корреляция; аудирование; assessment; онлайн-школа; listening; online school; testing; correlation